Basic electrophysical parameters of GaxIn1-xAs solid solution microwhiskers - Большакова, Інеса Антонівна; Кость, Ярослав Ярославович; Макідо, Олена Юріївна; Стецко, Роман Михайлович; Шуригін, Федір Михайлович (Eastern-European Journal of Enterprise Technologies, 2014)
The paper deals with the studying basic electrophysical parameters of GaхIn1-хAs solid solution microwhiskers, grown by the method of chemical transport reactions using the vapor-liquidcrystal mechanism, and their stability under the influence of ionizing (neutron) radiation. Such studies are interesting in terms of the efficiency of the method of growing these materials, model calculations of their parameters and identifying possible application fields. The results of studying the electrophysical parameters (the Hall coefficient, resistivity, mobility) of the grown GaxIn1-xAs microwhiskers in the composition range of 0.3≤x≤0.8 are given. The band gap value of the microwhiskers was calculated by the changes behavior of the electrophysical parameters in the zone of intrinsic and mixed conduction. The analysis of the radiation resistance of the grown microwhiskers was carried out on the basis of the local electroneutrality level calculation for GaxIn1 xAs solid solution with different composition and changes in the concentration of the intrinsic material charge carriers, determined before and after the neutron radiation at fluences of Fn = 1・1015 sm-2 та Fn = 7・1015 sm-2. It was found that in GaxIn1-xAs solid solution the sublattices of binary compounds retain their properties and under the influence of ionizing radiation can compensate the material changes by forming radiation defects (dopants) of different types (acceptor and donor), which allow developing radiation-resistant devices on their basis. So, GaхIn1-хAs solid solutions with the component composition of x ≤ 0.6 are interesting in terms of using for sensors, operating in radiation conditions that was experimentally confirmed.